Strategi Pembelajaran Pendidikan Agama Islam Bagi Siswa Autis Di SLB Putra Idhata Kabupaten Madiun - Affan Pradikta (Thawalib: Jurnal Kependidikan Islam, 2020)
This study aims to determine PAI learning and understand the problems and solutions of the application of Islamic Education learning for autism  students at SLB Putra Idhata, Madiun Regency. The research method used is a qualitative approach with the type of case study research and the thinking process uses inductive paragraphs. Data collection techniques using interviews, observation, and documentation. While the data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results showed that: (1) Learning on the autism students was adjusted to the abilities and characteristics of the students. The teaching of Islamic religious education for students on the autism uses the ABA (Applied Behavior Analysis) method. This therapy teaches children on the autism to follow verbal instructions, respond to other people's words, describe an object, imitate other people's words and movements. (2) The main obstacle to learning Islamic education for autism students is the incomplete target material, because students have difficulty concentrating for a long time. So before students can concentrate, instruction cannot be given. The solution is by modifying the material according to the students 'abilities, compiling creative and varied media so as to attract students' interest to concentrate in the teaching and learning process.